Comparison of Mesenchymal Stromal Cells From Different Origins for the Treatment of Graft-vs.-Host-Disease in a Humanized Mouse Model - Grégoire, Céline; Ritacco, Caroline; Hannon, Muriel; Seidel, Laurence; Delens, Loïc; Belle, Ludovic; Dubois, Sophie; Vériter, Sophie; Lechanteur, Chantal; Briquet, Alexandra; Servais, Sophie; Ehx, Gregory; et al. (Frontiers in Immunology, 2019)
Mesenchymal stromal cells (MSCs) have potent immunomodulatory properties that make them an attractive tool against graft-versus-host disease (GVHD). However, despite promising results in phase I/II studies, bone marrow (BM-) derived MSCs failed to demonstrate their superiority over placebo in the sole phase III trial reported thus far. MSCs from different tissue origins display different characteristics, but their therapeutic benefits have never been directly compared in GVHD. Here, we compared the impact of BM-, umbilical cord (UC-), and adipose-tissue (AT-) derived MSCs on T-cell function in vitro and assessed their efficacy for the treatment of GVHD induced by injection of human peripheral blood mononuclear cells in NOD-scid IL-2Rnull HLA-A2/HHD mice. In vitro, resting BM- and AT-MSCs were more potent than UC-MSCs to inhibit lymphocyte proliferation, whereas UC- and AT-MSCs induced a higher regulatory T-cell (CD4+CD25+FoxP3+) / T helper 17 ratio. Interestingly, AT-MSCs and UC-MSCs activated the coagulation pathway at a higher level than BM-MSCs. In vivo, AT-MSC infusions were complicated by sudden death in 4 of 16 animals, precluding an analysis of their efficacy. Intravenous MSC infusions (UC- or BM- combined) failed to significantly increase overall survival (OS) in an analysis combining data from 80 mice (hazard ratio [HR]=0.59, 95% confidence interval [CI] 0.32-1.08, P=0.087). In a sensitivity analysis we also compared OS in control versus each MSC group separately. The results for the BM-MSC versus control comparison was HR=0.63 (95% CI 0.30-1.34, P=0.24) while the figures for the UC-MSC versus control comparison was HR=0.56 (95% CI 0.28-1.10, P=0.09). Altogether, these results suggest that MSCs from various origins have different effects on immune cells in vitro and in vivo. However, none significantly prevented death from GVHD. Finally, our data suggest that the safety profile of AT-MSC and UC-MSC need to be closely monitored given their pro-coagulant activities in vitro.